An assessment of monetary policy response to capital inflows in Nigeria - Usman M. Okpanachi (CBN Journal of Applied Statistics, 2012)
Large and persistent capital inflows can be a double-edged sword. Accompanying its many attractions is the tendency to display a boom and bust pattern (volatility and reversals) in addition to the possibility of causing rapid exchange rate appreciation, inflation and loss of monetary policy independence. These downside risks create very strong impetus for some sort of policy response like sterilization, fiscal consolidation or controls. This study employs a simple analytical framework to estimate the intensity (and effectiveness) of monetary sterilization by the Central Bank of Nigeria (CBN) in response to increased capital inflows in recent years. The study finds evidence of less-than-full, but significantly high sterilization intensity, albeit no indication of sterilization smoothing by the Bank. The paper reports also, evidence of slacking sterilization over time, attributable in part to cost and financial system stability considerations. Rising cost of sterilization, especially, could soon undermine the sustainability of the current approach, predicated on a heavy reliance on market operations, should inflows of the magnitudes observed in the past persist. The situation calls for adoption of supplementary measures.
Keywords: E52; F21; F32; 330; Capital inflows; monetary policy; sterilization; sterilization index; sterilization intensity; Nigeria